Undermining of Democracy: Are Trade Agreements Flawed? - Shrestha, Aslesh (Campion Journal of Multidisciplinary Research and Explorer, 2025)
This article critically examines the role of modern trade agreements—specifically CETA, TPP, and TTIP—and their impact on the democratic sovereignty of member states through the controversial Investor-State Dispute Settlement (ISDS) mechanism. While ISDS was originally designed to protect foreign investors from unfair treatment, evidence suggests it increasingly empowers multinational corporations to challenge public-interest regulations and national policies outside domestic legal systems. Through a review of key cases such as Lone Pine vs. Canada and Vattenfall vs. Germany, the paper highlights how ISDS mechanisms have led to a phenomenon known as "regulatory chill," where governments refrain from enacting policies benefiting the public for fear of litigation. It also contrasts the critiques from civil societies with the defences offered by proponents of ISDS, such as the European Federation for Investment Law and Arbitration (EFILA). Ultimately, the article argues that unless trade agreements are reformed to safeguard democratic governance, multinational corporations will continue to erode the policy autonomy of sovereign states under the guise of investment protection.